PENGEMBANGAN SOSIAL EMOSI MELALUI CERITA UNTUK ANAK USIA DINI - Vivi Sufiati; Nur Hasanah (Jurnal CARE (Children Advisory Research and Education), 2021)
Abstract This research is a qualitative case study research conducted on PAUD teachers who have taken the socialemotional development course at UNIPMA for the 2019/2020 school year. The purpose of the research was to determine the social emotional development of the teacher through stories. The research data were collected by means of observation, interviews, and document analysis. Observations were made to determine teacher practices in using stories to stimulate children's social emotions. Interviews were conducted to find out how the teacher's social emotional development was carried out with stories. Document analysis was carried out by analyzing story script documents made by the teacher and teacher assessment notes on storytelling activities. The results of the study found that the teacher told stories both at the beginning, at the core and at the end of the activity. Stories can be spontaneous and programmed. Immediate spontaneous activity without being planned. Programmed activities by planning stories for the development of social emotions into learning and assessing these activities. Exemplary activities are carried out by characterizing the stories. The characters shown in the story are in accordance with the basic competencies of social emotional self-confidence, obeying the rules for discipline, patience, independence, care and help, cooperation, and responsibility. Reference stories from story books, folk tales and make your own stories from social emotional development. Pre-story activities consist of determining story material, determining references, and making modifications, and supporting media to improvise in storytelling. Abstrak Penelitian ini merupakan penelitian kualitatif studi kasus yang dilakukan kepada guru PAUD yang sudah menempuh mata kuliah pengembangan sosial emosi di UNIPMA tahun ajaran 2019/2020. Tujuan dari penelitian untuk mengetahui pengembangan social emosi yang dilakukan guru melalui cerita. Data penelitian dikumpulkan dengan metode observasi, wawancara, dan analisis dokumen. Observasi dilakukan untuk mengetahui praktik guru dalam menggunakan cerita untuk stimulasi social emosi anak. Wawancara dilakukan untuk mengetahui bagimana pengembangan social emosi yang dilakukan guru dengan cerita. Analisis dokumen dilakukan dengan menganalisis dokumen naskah cerita yang dibuat guru dan catatan penilaian guru pada kegiatan bercerita. Hasil penelitian menemukan bahwa guru bercerita baik diawal, inti maupun penutup kegiatan. Cerita dapat dilakukan secara spontan dan terprogram. Kegiatan spontan langsung tanpa direncanakan. Kegiatan terprogram dengan merencanakan bercerita untuk pengembangan social emosi kedalam pembelajaran dan melakukan penilaian pada kegiatan tersebut. Kegiatan keteladanan dilakukan dengan penokohan yang ada dalam cerita. Karakter yang ditunjukkan dalam cerita sesuia dengan kompetensi dasar social emosi percaya diri , taat aturan untuk disiplin, sabar, mandiri, peduli dan tolong menolong, kerjasama, dan tanggung jawab. Referensi cerita dari buku cerita, cerita rakyat dan membuat cerita sendiri dari pengembangan social emosi. Kegiatan pracerita terdiri dari menentukan materi cerita, menentukan referensi, dan melakukan modifikasi, dan media pendukung untuk improvisasi dalam bercerita.